Changes in the anti-oxidant system in adult epilepsy patients receiving anti-epileptic drugs. (July 2015) - Işık, Mesut; Demir, Yeliz; Kırıcı, Mahinur; Demir, Recep; Şimşek, Fatma; Beydemir, Şükrü
Abstract Anti-epileptic drugs (AEDs) have been widely used in patients with epilepsy. This study evaluated the adverse effects of two commonly prescribed AED monotherapies, carbamazepine (CBZ) and valproic acid (VPA). The aim of this study was to evaluate the influence of these anti-epileptic drugs on paraoxonase-1 (PON-1), glutathione S-transferase (GST) and acetyl cholinesterase (AChE) activities in the serum of adult patients with epilepsy. Of the 56 epileptic adults, 28 were given valproate, and the remaining 28 were given carbamazepine. Glutathione (GSH) levels in epilepsy patients receiving anti-epileptic drug treatment were insignificantly higher compared with controls. GST activity in epilepsy patients receiving anti-epileptic drug treatment was insignificantly lower compared with controls. PON1 and AChE activity in epilepsy patients receiving anti-epileptic drug treatment was significantly lower compared with controls. PON1 and AChE activities in the serum of patients treated with carbamazepine monotherapy were lower than in patients treated with valproic acid monotherapy.